Prognostic value of serum inflammatory markers in patients with esophageal squamous cell carcinoma undergoing surgery: a two-center retrospective cohort study - Yaqin Dong; Fan Wang; Jiaying Deng; Tong Tong; Xiangxun Chen; Liming Wu; Yichun Wang; Mei Kang; Yutong Xu; Guangjie Shi; Liyang Zhu (BMC Cancer)
Abstract Background and purpose The combined assessment of the neutrophil-platelet score and prognostic nutritional index is yet to be applied in evaluating the prognosis of patients following an operation for esophageal cancer. This study aimed to identify independent prognostic factors for patients undergoing operation for esophageal cancer and to construct a nomogram model for predicting median overall survival (mOS). Methods A cohort of 660 patients with esophageal cancer from two clinical centers in China was recruited, comprising a training cohort (n = 511) and a validation cohort (n = 149). Survival rates were compared using Kaplan–Meier curves and the log-rank test. The Cox regression model was used to identify independent prognostic factors. Results The Multi-variable Cox regression analysis revealed that tumor, node, metastasis stage, smoking status, neutrophil-platelet score, and prognostic nutritional index were independent postoperative prognostic factors for patients with esophageal cancer (P < 0.05). The mOS (129.0 months, 95% confidence interval (CI) not reached) was significantly higher in patients with a low neutrophil-platelet score than those with a high score (43.0 months, 28.1–57.9; P < 0.05). Conversely, the mOS (42.0 months, 95% CI 6.7–55.2) was lower in the low prognostic nutritional index score group than the high score group (125.0 months, 95% CI 96.4–153.6; P < 0.05). Evaluation metrics, including the concordance index (0.69 in the training group and 0.70 in the validation group), receiver operator characteristic curve analysis (In the training cohort, the AUCs for predicting 1-, 3-, 5- and 10-year overall survival rates using the nomogram were 76.19%, 69.07%, 70.12% and 68.17%, respectively; in the validation cohort, the corresponding predicted values were 76.66%, 77.18%, 75.04% and 79.57%, respectively), calibration curve, and decision curve analysis, demonstrated the clinical utility of the constructed prediction model. Conclusions Serving as systemic inflammatory biomarkers, the neutrophil-platelet score and prognostic nutritional index offer valuable prognostic insights for patients with esophageal cancer, augmenting predictive capabilities.